Stakeholder participation in innovation platform and implications for Integrated Agricultural Research for Development (IAR4D) - Nyikahadzoi, Kefasi; Pali, Pamela N.; Fatunbi, A.O.; Olarinde, L.O.; Njuki, Jemimah; Adekunle, A.O. (Scientific and Academic Publishing, 2012)
In sub-Saharan Africa, there is increasing interest for the adaptation and use of the innovation systems approach to advance learning and development in the Agricultural Research and Development (ARD) sector. This crave is constrained by unavailability of a proven blue print that describe the paradigm shift from the linear approach and how such could function under different socio-economic, cultural and political climate. This paper uses three case studies from the Sub Saharan Africa Challenge Program (SSA CP) to accentuate approaches and strategies for the successful use of the innovation system approach in agricultural research and development. The paper shows that the establishment of Innovation Platforms under the premise of Integrated Agricultural Research for Development (IAR4D) at the grass-root uses social networks and capital to mobilize for collective action necessary to meet market demand. It also shows that the ensued iterative structure is suitable for dealing with policy issues that constrain value chain at district level, while the apex structure is functional in dealing with policy issues at national and regional level. This paper proposes a coordinated ARD strategy that links innovation platforms at the continental, sub-regional, national and the grass root as the best practices for comprehensive use of innovation system approach.